2007
DOI: 10.1093/nar/gkl917
|View full text |Cite
|
Sign up to set email alerts
|

Use of signal sequences as an in situ removable sequence element to stimulate protein synthesis in cell-free extracts

Abstract: This study developed a method to boost the expression of recombinant proteins in a cell-free protein synthesis system without leaving additional amino acid residues. It was found that the nucleotide sequences of the signal peptides serve as an efficient downstream box to stimulate protein synthesis when they were fused upstream of the target genes. The extent of stimulation was critically affected by the identity of the second codons of the signal sequences. Moreover, the yield of the synthesized protein was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Thus, it can be speculated that the presence of the melittin signal sequence at the 5 end of the target gene stabilizes the initiation activity and translational processivity, resulting in significantly increased protein yields. This interpretation is also supported by a publication, in which the authors have shown the stimulatory effect of signal sequences on protein synthesis efficiency in an E. coli-based cell-free protein synthesis system [42]. Interestingly, the stimulatory effect of the signal sequence was mainly dependent on the identity of its second codon.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Thus, it can be speculated that the presence of the melittin signal sequence at the 5 end of the target gene stabilizes the initiation activity and translational processivity, resulting in significantly increased protein yields. This interpretation is also supported by a publication, in which the authors have shown the stimulatory effect of signal sequences on protein synthesis efficiency in an E. coli-based cell-free protein synthesis system [42]. Interestingly, the stimulatory effect of the signal sequence was mainly dependent on the identity of its second codon.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, the stimulatory effect of the signal sequence was mainly dependent on the identity of its second codon. In particular, in most effective signal sequences, position +2 was occupied by the codon AAA , an observation that also accounts for the melittin signal sequence that was applied in this study . Although melittin‐fused antibody fragments could be produced in sufficient amounts, only very weak binding or no binding at all was detected for these scFv molecules.…”
Section: Discussionmentioning
confidence: 90%
“…Although the enzyme was successfully produced and secreted when it was cloned with its original signal peptide for secretion, best results were obtained when this peptide was replaced by the host's phoA signal peptide ( Supplementary Fig. S3; Ahn et al, 2006). The highest overexpression, assessed by clear zone halos produced by E. coli supernatants on PHB agarose plates, were obtained after 72 h of incubation after inducing with 1 mM of IPTG at 27 C ( Supplementary Fig.…”
Section: Alc24_4107 Has a Promiscuous Hydrolytic Activity On Aliphatimentioning
confidence: 99%
“…d (+) indicates absorbance greater than to blank control (PNGase treated and untreated, see Figure S2) sample absorbance's for each respective lectin 1-12. Others have reported the comparable yields of EPO with human signal peptide using the E. coli cell-free system (Ahn et al, 2007). (−) indicates absorbance values that are less than blank control (PNGase treated and untreated, see Figure S2) sample absorbance's for each respective lectin 1-12.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators (Table 1) have used the E. coli CFPS, insect CFPS and CHO CFPS systems for the expression of human EPO (Ahn, Choi, & Kim, 2005;Ahn, Hwang, Lee, Choi, & Kim, 2007;Brodel, Sonnabend, & Kubick, 2014;Brodel, Wustenhagen, & Kubick, 2015;Stech et al, 2014). However, no further optimization studies were reported.…”
mentioning
confidence: 99%